Artificial Intelligence and Theology: Looking for a Positive—but Not Uncritical—Reception - Oviedo Torró, Lluís (Zygon, 2022)
Theology and other human sciences present concerns against artificial intelligence (AI) that are often limited to ethical issues, as they appear as the most pressing problems and challenges derived from these new technologies. However, by reviewing the published literature, the article shows that theologians have ventured into broader areas, with a specific focus on the anthropological consequences of current technological advances. New developments and achievements in AI invite further exploration from a theological perspective, and they offer some opportunities and useful applications for theologians. The article moves from the ethical territory toward the more neutral but highly engaging dialogue between science, technology, and religion, their interactions and mutual enrichment. Within this transdisciplinary area, new insights are gained about the role a more committed theology can play in issues like designing the best approaches between religious faith and intelligent systems to achieve a sustainable and equitable future.